2021
DOI: 10.1016/j.jaim.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-balancing and protective effect of combined extract of Sauropus androgynus and Elephantopus scaber against Escherichia coli-induced renal and hepatic necrosis in pregnant mice

Abstract: Background Elephantopus scaber (ES) and Sauropus androgynous (SA) have been frequently reported to possess antibacterial activity through in vitro, but in vivo studies about the protective effect of combined ES and SA have acquired less attention. Objectives To evaluate protective effect of combined ethanol extract of ES and SA on hormone imbalance and renal and hepatic necrosis formation in Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…This study revealed that FSH levels in infected pregnant mice were increased significantly after receiving combined ES and SA at a ratio of 25:75 (Table-1). However, in a previous study [9], estrogen levels were stable after receiving E. coli injection along with ES and SA in combination. Several factors may explain these differences in estrogen levels after E. coli infection.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…This study revealed that FSH levels in infected pregnant mice were increased significantly after receiving combined ES and SA at a ratio of 25:75 (Table-1). However, in a previous study [9], estrogen levels were stable after receiving E. coli injection along with ES and SA in combination. Several factors may explain these differences in estrogen levels after E. coli infection.…”
Section: Discussionmentioning
confidence: 65%
“…Christina et al [9] demonstrated that E. coli infection increases fetal reabsorption and decreases serum progesterone levels, which are needed during a normal mouse pregnancy. Their study suggested that hormonal changes during pregnancy produced an adverse effect [9]. The use of a powerful natural bioactive compound from plants is urgently needed to prevent the adverse effects of E. coli infection during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations